The Effect of Financial Leverage on Financial Performance -Survey Study on Companies Listed in Damascus Stock Exchange- (Latakia University Journal - Economic and Legal Sciences Series, 2023)
The study aimed to identify the effect of financial leverage measured by the ratio of assets to equity on financial performance measured by three indicators: return on assets, return on equity, and return on investment.To achieve this aim; Secondary data was collected from the annual financial reports of the companies listed on the Damascus Stock Exchange and available on the official website of that market, and the data was analyzed using the Eviews 10 program, and the study used cross-sectional data.The number of these companies reached 19 during the period from 2013 to 2020, with a total of 152 observations.The results showed a positive effect of financial leverage measured by the ratio of financing assets through equity in each of the return on assets, return on equity, and return on investment.